Amycolatopsis samaneae sp. nov., isolated from roots of Samanea saman (Jacq.) Merr - Kannika Duangmal (2018)
A novel actinomycete, designated strain RM287T, was isolated from surface-sterilized roots of Samanea saman (Jacq.) Merr., collected from Bangkok, Thailand. The status of the novel strain was determined using a polyphasic taxonomic approach. Phylogenetic analyses based on 16S rRNA gene sequences showed that the organism formed a distinct phyletic line within the radiation of the genus Amycolatopsis. The 16S rRNA gene sequence similarity indicated that strain RM287T was most closely related to Amycolatopsis mediterranei IMSNU 20056T (97.4%), A. rifamycinica DSM 46095T (97.2%), A. kentuckyensis NRRL B-24129T (97.2%), A. pretoriensis DSM 44654T (97%) and A. australiensis DSM 44671T (97%). The novel organism was found to have chemical properties typical of members of the genus Amycolatopsis such as meso-diaminopimelic acid as the dignostic diamino acid in the cell-wall peptidoglycan and arabinose and galactose as the diagnostic sugars. The major menaquinone was MK-9(H4). The major fatty acids were iso-C16: 0 iso-C15: 0, iso 2-OH-C16: 0 and iso-C17: 0. The DNA G+C content was 71.7 mol%. Phenotypic data clearly distinguished the novel isolate from its closest relatives. The combined genotypic and phenotypic data indicated that strain RM287T represented a novel species of the genus Amycolatopsis. The proposed name for this organism is Amycolatopsis samaneae sp. nov., with the type strain RM287T (5TISTR 1919T5BCC 35842T5NBRC 106095T). © G 2011 IUMS.